Spatial distribution of microbial communities in the shallow submarine alkaline hydrothermal field of the Prony Bay, New Caledonia. Issue 6 (9th July 2014) - Quéméneur, Marianne; Bes, Méline; Postec, Anne; Mei, Nan; Hamelin, Jérôme; Monnin, Christophe; Chavagnac, Valérie; Payri, Claude; Pelletier, Bernard; Guentas‐Dombrowsky, Linda; Gérard, Martine; Pisapia, Céline; et al.
Summary The shallow submarine hydrothermal field of the Prony Bay (New Caledonia) discharges hydrogen‐ and methane‐rich fluids with low salinity, temperature (< 40°C) and high pH (11) produced by the serpentinization reactions of the ultramafic basement into the lagoon seawater. They are responsible for the formation of carbonate chimneys at the lagoon seafloor. Capillary electrophoresis single‐strand conformation polymorphism fingerprinting, quantitative polymerase chain reaction and sequence analysis of 16S rRNA genes revealed changes in microbial community structure, abundance and diversity depending on the location, water depth, and structure of the carbonate chimneys. The low archaeal diversity was dominated by few uncultured Methanosarcinales similar to those found in other serpentinization‐driven submarine and subterrestrial ecosystems (e.g. Lost City, The Cedars). The most abundant and diverse bacterial communities were mainly composed of Chloroflexi, Deinococcus‐Thermus, Firmicutes and Proteobacteria. Functional gene analysis revealed similar abundance and diversity of both Methanosarcinales methanoarchaea, and Desulfovibrionales and Desulfobacterales sulfate‐reducers in the studied sites. Molecular studies suggest that redox reactions involving hydrogen, methane and sulfur compounds (e.g. sulfate) are the energy driving forces of the microbial communities inhabiting the Prony hydrothermal system.